Cross-national comparison of monetary and multidimensional child poverty in the European Union : puzzling with the few pieces that the EU-SILC provides /: puzzling with the few pieces that the EU-SILC provides. (November 2010) - Notten, Geranda; Roelen, Keetie, 1981-
No abstract available